Respuesta :
Answer:
x = -1
y = -2
Step-by-step explanation:
5x + 2y = -9 2y = -9 - 5x y=(-9-5x)/2
3x + 4y = -11
3x+4[(-9-5x)/2] = -11
3x+( -36-20x)/2 = -11
3x-18-10x = -11
-7x = 7
x = -1
y = -2
Answer:
x = −1 and y = −2
Step-by-step explanation:
Utilicé sustitución.
Mire las imágenes para obtener una explicación paso a paso.
![Ver imagen arianna9625](https://us-static.z-dn.net/files/de3/677efcc61504534326f28f03a208ceb3.png)
![Ver imagen arianna9625](https://us-static.z-dn.net/files/d37/92032c578d10271fb4513562c709ed39.png)
![Ver imagen arianna9625](https://us-static.z-dn.net/files/d60/0f16614c7bade098e3c713a0eb5b0ea6.png)